American Perspective on the Quality of Democracy in Poland - Jureńczyk, Łukasz (Historia i Polityka, 2023)
The American model of democracy is identified with liberal democracy, which in the West is usually considered a democracy of the highest quality standards. The illiberal authorities in Poland criticize this model of democracy, introducing a number of legal changes which, in their opinion, are to lead to an improvement in the quality of democracy. American researchers quite unequivocally criticize the changes, especially those taking place in the area of independence of the judiciary, freedom of the media and women’s rights. They also criticize the attitude of the Polish authorities towards minorities, including LGBTQ+ communities. Criticism also appeared from the American authorities, although in this case we were dealing with a large variation in the approach of individual administrations. The aim of the article is to analyze and evaluate the American perspective on the quality of democracy in Poland. During the research, scientists and experts from research institutions in Washington, D.C. and New York were interviewed.